DEVELOPMENT OF EMOTIONAL INTELLIGENCE IN THE ASPECT OF PERSONALITY DEVELOPMENT IN THE CONTEXT OF A LEARNING ORGANIZATION - Garbenis, Simas; Palujanskienė, Paulina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Today`s schools coexist with an environment that is constantly changing and shifting that is why modern schools should be open to new experiences, possibilities, become learning organizations. Also, educational institutions face the need for competencies in the formulation and implementation of competition policy, which in itself requires managerial knowledge based on an innovative approach. Moreover, the development of emotional intelligence integrated with the school curricula should be considered as one of the criteria for a school to become a learning school. Although some robust knowledge already exists about the positive impact of emotional intelligence development in educational settings. There is little to no research and theoretical data about the means to successfully integrate emotional intelligence development in schools as a context of learning organizations. Moreover, there is not any strong theoretical framework that links several ideas and theories on which they need for emotional intelligence development in learning schools could be based upon. Regarding this knowledge gap, this article aims to reveal the attitude of school staff about the development of emotional intelligence in the context of a school-learning organization. To achieve this goal, methods were used: scientific analysis of literature and documents and theoretical interpretations. Research results: peculiarities of emotional intelligence development in the context of personality development in the context of learning organization: how emotional intelligence is developed, its meaning and importance, possible perspectives, benefits for personality and organization-school in the context of learning organization (L. Vygotsky theoretical aspect). This justifies the need to organize personnel management and professional development processes in the development of emotional intelligence.